THE EFFECT OF FINANCIAL KNOWLEDGE, INCOME, SOCIAL INFLUENCE, PERCEPTION OF EASE AND PERCEPTION OF USEFULNESS ON THE DECISIONS OF SHOPEE PAYLATER USERS IN EAST BEKASI - Putri Ayu Lestari; Muhammad Richo Rianto; Eri Bukhari (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to measure the direct effect and indirect effect of financial knowledge, income, social influence, perception of ease, and perception of usefulness on the decisions of shopee paylater users in east bekasi. The results of this study provide an explanation that the variables of financial knowledge, social influence and perceived of usefulness have a positive effect on shopee paylater user decisions in East Bekasi. However, the variables of income and perceived of ease have no effect on shopee paylater user decisions, this study shows that income and perceived of ease are not the main considerations in using shopee paylater.